Transcriptomic Overview of Comparative Multi-Scale Biocompatibility of ZrO2 and Y-TZP Alloys - Tchinda , Alex; Chézeau, Laëtitia; Pierson , Gaël; Kouitat-Njiwa, Richard; Rihn, B. H.; Bravetti, Pierre (Chemical and Materials Sciences - Developments and Innovations Vol. 2, 2024)
The present study assesses the biocompatibility of pure zirconia discs ZrO2 compared to yttria–zirconia discs (Y-TZP) as well as the influence of the surface topography through the combination of a conventional toxicological assay, morphological observations, and a transcriptomic analysis on an in vitro model of human Saos-2 bone cells. The direct anatomical and functional bond between the surface of an implant and living neoformed bone is known as the osseointegration of implants. Implants' biological compatibility is contingent upon a number of factors, including surface topography, chemical composition, material type, and mechanobiological characteristics. Similar cell proliferation rates were observed between ZrO2 and Y-TZP discs and control cells, independent of surface topography, for up to 96 hours of exposure. High cell density was similarly observed on the surfaces of both materials. It could be interesting to perform a comparative transcriptomic study between rough and mirror-polished Y-TZP samples to observe a potential influence of the surface topography on the gene expression and to better understand the underlying mechanisms. Relevantly, only 110 transcripts were differentially expressed across the human transcriptome, consistent with the excellent biocompatibility of Y-TZP reported in the literature. These deregulated transcripts are mainly involved in two known metabolic pathways, the first being linked to 'mineral absorption' and the second to 'immune response'. These observations suggest that Y-TZP is an interesting candidate for application in implantology. Y-TZP is a serious candidate for implantology in general. However, further biocompatibility and biomechanical studies are needed to position Y-TZP as a reference material in oral implantology and to find the best roughness level for this material.